Perluasan Hutan Mangrove dalam Mitigasi Risiko Bencana Pemanasan Global: Kegiatan PkM di Kawasan Pesisir Muara Angke Jakarta - Rukaesih A. Maolani; Achmad Sudiyar Dalimunthe; Dwi Haryanto; Rivo Bifa; Putri Azzahra; Cornelia Juwita; Putu Egawastu Suryamika (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
One of the disasters caused by humans is global warming. Global warming is a big problem that is being faced by all human beings and living things on earth. One of the activities that can be carried out in mitigating the risk of global warming is through Mangrove Ecosystem Rehabilitation. The existence of the Mangrove ecosystem in the coastal area of ​​DKI Jakarta Province is currently experiencing a decline in line with the development that changes the function of the area from a protected function to a cultivation function. One area that has experienced this is the coastal area in Muara Angke which has had a negative impact on the environment, namely the function of protecting and securing the coast will naturally be lost. In this 2021 Community Service program, STMA Trisakti has participated in helping to solve the problem of the rate of degradation of the Mangrove Forest by planting 1000 mangrove seedlings in the Muara Angke Eco-tourism area. The planting was carried out on World Environment Day on 5 June 2021.